PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, DAN BIAYA OPERASIONAL TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Pramachningtyas, Aldillah; Faturokhman, Agus; Sunarmo, Agus; Warsidi, Warsidi (Jurnal Riset Akuntansi Soedirman, 2024)
The purpose of this study is to determine and analyze the effect of profitability, company growth, and operational costs on corporate social responsibility disclosure. The population of this study is mining companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The sample of this study was 17 companies obtained using the purposive sampling method. This research data is secondary data obtained through the company's annual report, so that the data obtained during the research period is 102 research data. Data analysis uses panel data regression, descriptive statistics, classical assumption tests, and hypothesis tests. The selection of the panel data regression model was carried out through three tests, namely the chow test, the hausman test, and the muptilier langrange test. There are three types of panel data regression models, namely fixed effect models, common effect models, and random effect models. Based on the testing of chow, hausman, and langrage multiplier, the appropriate regression model is the random effect model. Based on the results of research and data analysis using E-views 10, it is shown that: (1) Profitability has a positive and significant influence on corporate social responsibility disclosure; (2) The Company's growth has a negative and insignificant effect on the disclosure of corporate social responsibility; (3) Operational Costs have a positive and insignificant effect on corporate social responsibility disclosure.